2016
DOI: 10.1093/icc/dtw041
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of R&D networks

Abstract: Drawing on a large database of publicly announced R&D alliances, we empirically investigate the evolution of R&D networks and the process of alliance formation in several manufacturing sectors over a 24-year period (1986-2009). Our goal is to empirically evaluate the temporal and sectoral robustness of a large set of network indicators, thus providing a more complete description of R&D networks with respect to the existing literature. We find that most network properties are not only invariant across sectors, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
58
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 60 publications
(138 reference statements)
11
58
1
Order By: Relevance
“…However, neither the network endogeneity nor the exogenous partner selection, taken independently, are able to explain the topology of observed R&D networks. Endogenous mechanisms alone would lead to more and more centralized network structures over time, which we do not observe in reality6. On the other hand, exogenous mechanisms alone would lead to more regular networks topologies, which we do not observe neither.…”
contrasting
confidence: 84%
See 2 more Smart Citations
“…However, neither the network endogeneity nor the exogenous partner selection, taken independently, are able to explain the topology of observed R&D networks. Endogenous mechanisms alone would lead to more and more centralized network structures over time, which we do not observe in reality6. On the other hand, exogenous mechanisms alone would lead to more regular networks topologies, which we do not observe neither.…”
contrasting
confidence: 84%
“…However, these clusters are not isolated; previous studies69 have detected the existence of “shortcuts” connecting different clusters, as well as the formation of alliances with new partners not yet belonging to the R&D network. This observation suggests that firms diversify some of their alliances, rather than just establishing collaborations within a specific cluster.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…König et al, 2014a;König et al, 2011], 2 providing an explanation for why nestedness has been observed in empirical R&D networks [Tomasello et al, 2016]. Nested split graphs further have a core-periphery structure, which has also been documented in empirical studies on R&D networks [cf.…”
Section: Introductionmentioning
confidence: 72%
“…Moreover, the corresponding adjacency matrix is stepwise, characterizing a nested split graph, 28 and becomes increasingly sparse with increasing linking costs ζ. The fact that empirical R&D networks are characterized by nestedness has been documented in Tomasello et al [2016]. Further, note that nested split graphs are paramount examples of core-periphery networks.…”
mentioning
confidence: 99%